Improving the clearance of serious crime: the case of aggravated assault. Issue 4 (30th April 2021) - Scott, Thomas; Wellford, Charles
Abstract : Purpose: This paper addresses the clearance of aggravated assaults (AAs). Specifically, the authors consider variations in these clearances over time for large agencies and test which crime, investigation and agency factors are associated with the likelihood of clearance by arrest or exceptional means. In doing this work, they seek to extend the understanding of how police can improve their investigations and ability to solve serious offenses. Design/methodology/approach: Using case, investigative and organizational data collected from seven large police departments selected on the basis of their trajectory of index crime clearances, and measures of case characteristics, investigative effort and organizational best practices, this paper uses descriptive and inferential statistics to analyze AA investigations and case clearance. Findings: Key findings include the following: trajectories of AA clearance vary across large agencies and covary with a measure of organizational best practices, and the relationship between investigative effort and case clearance can depend on organizational practices. The authors find that measures of investigative effort are either not related to case clearance or there is a negative association. Research limitations/implications: Now that police researchers have a better understanding of AAs and their investigations, they need to test how this knowledge can be used to improve the quality of police investigations. Tests, preferably multi-agency randomized control trials, of new investigative strategies and organizational practices are needed. Originality/value: This research is original in that it uses a multi-agency sample and crime, investigation and organizational measures to understand AA clearance.